2017 ACC/AHA blood pressure classification and incident peripheral artery disease: The Atherosclerosis Risk in Communities (ARIC) Study. (29th August 2020) - Lu, Yifei; Ballew, Shoshana H; Tanaka, Hirofumi; Szklo, Moyses; Heiss, Gerardo; Coresh, Josef; Matsushita, Kunihiro
Abstract: Aims: The aim of this study was to evaluate the associations of blood pressure categorization based on the 2017 American College of Cardiology and American Heart Association guideline with the risk of peripheral artery disease (PAD). Methods: Among 13, 113 middle-aged participants, we investigated the associations of 2017 blood pressure categories (systolic <120 and diastolic <80 mmHg (normal if no anti-hypertensive medications; reference), 120–129 and <80 (elevated), 130–139 and/or 80–89 (stage 1 hypertension), and ≥140 and/or ≥90 (stage 2 hypertension)) with incident PAD (hospitalizations with a diagnosis or leg revascularization) using Cox regression models. Analyses were separately conducted in individuals with and without anti-hypertensive medications. Results: During a median follow-up of 25.4 years, 466 incident PAD occurred (271 cases in 9858 participants without anti-hypertensive medications). In participants without anti-hypertensive medications, we observed significant hazard ratios of PAD in elevated blood pressure (1.80 (1.28–2.51)) and stage 2 hypertension (2.40 (1.72–3.34)), but not in stage 1 hypertension. Analyzing systolic and diastolic blood pressure separately, higher systolic blood pressure categories showed significant associations with incident PAD in a graded fashion whereas, for diastolic blood pressure, only ≥90 mmHg did. Generally similar patterns were seen among participants on anti-hypertensive medication, while they had higher risk of PAD than those without at each blood pressure category. Conclusions: Systolic blood pressure, including the category of 130–139 mmHg, showed stronger associations with incident PAD than did diastolic blood pressure. Consequently, elevated blood pressure conferred similar or even greater risk of PAD than stage 1 hypertension, with implications on how to interpret new blood pressure categories in terms of leg vascular health.